PENCATATAN PERKAWINAN: Melacak Akar Budaya Hukum dan Respon Masyarakat Indonesia terhadap Pencatatan Perkawinan - Lathifah, Itsnaatul (UIN Sunan Kalijaga Yogyakarta, 2015)
Marriage is basically valid when it has qualified and fulfill its requirements, namely the bridegroom, guardian for the bride, the presence of two witnesses, and ijab-qabul (contract of marriage). In modern life, particularly in Indonesia, the marriage will not be considered valid not only when it has fulfilled the pillars of marriage, but rather that the marriage must also be registered (recorded). Perncatatn marriage this is a debate among the public. Most accept it as a positive thing and contains benefits for married couples, while others refused because it is considered not in harmony with religious requirements in terms of marriage; that no one nash, either in the Qur'an or hadith of the Prophet which requires that the marriage should be registered. This article discusses differences in views among the Muslim community in Indonesia related to Marriage Registration issues as stipulated in Law on Marriage No. 1 of 1974; the arguments put forward by each party, and also the culture of law in Indonesia that contributed to the emergence of a difference in addressing this.